Strategies for developing novel therapeutics for sensorineural hearing loss - Nakagawa, Takayuki (Frontiers in Pharmacology, 2014)
Sensorineural hearing loss (SNHL) is a common disability in the world; however, at present, options for the pharmacological treatment of SNHL are very limited. Previous studies involving human temporal bone analyses have revealed that the degeneration of the cochlea is a common mechanism of SNHL. A major problem for the development of novel pharmacotherapy for SNHL has been the limited regeneration capacity in mammalian cochlear cells. However, recent progress in basic studies has led to several effective strategies for the induction of regeneration in the mammalian cochlea, in accordance with the stage of degeneration. In addition, recent advances in the identification of human deafness genes and their characterization in mouse models have elucidated cellular and/or molecular mechanisms of SNHL, which will contribute to clarify molecular targets of pharmacotherapy for treatment of SNHL.